Call Of Nature: Exploring The Impact Of Environmental Sustainability Orientation On Environmental Performance Through Environmental Innovation In Canggu Tourism Village - Kurniasari, Ni Made Dyah Ryana; Putri, Jellycha Mutiara Kurnia; Yudhistira, Putu Gde Arie (Journal of Tourism Sustainability, 2024)
Canggu Tourism Village, a rapidly growing tourism destination, faces significant challenges in maintaining a balance between economic growth and environmental conservation. In this context, adopting an environmental sustainability orientation becomes critical to ensuring that economic activities do not negatively affect the environment. This study investigates the impact of environmental sustainability orientation on environmental performance in Canggu Tourism Village, with a focus on the mediating role of environmental innovation and the moderating effect of environmental hostility. A quantitative approach was employed, collecting data from 122 tourism actors through a structured questionnaire using a judgment sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, examining both the outer and inner models. The findings reveal that environmental sustainability orientation significantly enhances environmental performance, both directly and indirectly, through environmental innovation. However, environmental hostility does not moderate the relationship between environmental sustainability orientation and environmental performance. These results underscore the importance of fostering environmental innovation as a pathway to sustainable tourism development, even in the face of external environmental challenges.